2020
DOI: 10.3390/ijms21020540
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1, a Proresolving Lipid Mediator, Ameliorates Liver Ischemia-Reperfusion Injury and Stimulates Hepatocyte Proliferation in Sprague-Dawley Rats

Abstract: Maresin-1 (MaR1) is a specialized pro-resolving mediator, derived from omega-3 fatty acids, whose functions are to decrease the pro-inflammatory and oxidative mediators, and also to stimulate cell division. We investigated the hepatoprotective actions of MaR1 in a rat model of liver ischemia-reperfusion (IR) injury. MaR1 (4 ng/gr body weight) was administered prior to ischemia (1 h) and reperfusion (3 h), and controls received isovolumetric vehicle solution. To analyze liver function, transaminases levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 62 publications
1
31
1
Order By: Relevance
“…We con rmed that MaR1-treated mice exhibited decreased hepatocyte apoptosis compared with controls after liver I/R. However, this is contradictory to previous ndings in a rat liver I/R model, where protein expression of cleaved caspase-3 was dramatically increased with MaR1 treatment (Soto et al 2020). The reason for the contradictory results is unclear and may be related to species differences, time of treatment with MaR1, or potential adverse/toxic effects of MaR1 in the previously-published study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We con rmed that MaR1-treated mice exhibited decreased hepatocyte apoptosis compared with controls after liver I/R. However, this is contradictory to previous ndings in a rat liver I/R model, where protein expression of cleaved caspase-3 was dramatically increased with MaR1 treatment (Soto et al 2020). The reason for the contradictory results is unclear and may be related to species differences, time of treatment with MaR1, or potential adverse/toxic effects of MaR1 in the previously-published study.…”
Section: Discussioncontrasting
confidence: 86%
“…Recently, a number of studies have revealed that MaR1 exerts powerful anti-in ammatory and pro-resolving effects in several disease models by promoting the resolution of in ammation through reduced neutrophil in ltration and improved macrophage phagocytic activity without causing immunosuppression (Han et al 2019, (Gong et al 2015, (Buckley et al 2014. Furthermore, studies also show that MaR1 has protective effects on I/R injury in several organs including the liver in a rat model (Soto et al 2020). However, the mechanisms of the protective effects of MaR1 in hepatic I/R injury have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…By means of the numbers of mitoses found, it was observed that hepatic hyperplasia was ongoing in G1 and G2, as this number was significantly high when compared with data from the literature (14) . However, in the groups that received treatment with rutin (G1) there was a significant increase in the number of mitoses after 24 hours (P=0.0022) and 48 hours (P=0.0152), indicating that the treatment contributed to the stimulation of hyperplasia.…”
Section: Mitosis and Apoptosismentioning
confidence: 70%
“…MaR1, another member of SPMs, promotes the nuclear translocation of NRF2 in Sprague–Dawley mice, improves hepatic ischemia-reperfusion injury and stimulates hepatocyte proliferation [ 188 ]. MaR1 also modulates the NRF2 and TLR4/NF-κB signaling pathways to relieve dextran sulfate sodium-induced ulcerative colitis [ 189 ].…”
Section: Specialized Pro-resolving Lipid Mediators and Cardiac Fibmentioning
confidence: 99%